If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -25 = 4(x + -1) Reorder the terms: -25 + -3x = 4(x + -1) Reorder the terms: -25 + -3x = 4(-1 + x) -25 + -3x = (-1 * 4 + x * 4) -25 + -3x = (-4 + 4x) Solving -25 + -3x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -25 + -3x + -4x = -4 + 4x + -4x Combine like terms: -3x + -4x = -7x -25 + -7x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -25 + -7x = -4 + 0 -25 + -7x = -4 Add '25' to each side of the equation. -25 + 25 + -7x = -4 + 25 Combine like terms: -25 + 25 = 0 0 + -7x = -4 + 25 -7x = -4 + 25 Combine like terms: -4 + 25 = 21 -7x = 21 Divide each side by '-7'. x = -3 Simplifying x = -3
| 8x^3-20x^2-2x+5=0 | | -6=-3+x | | 2x+6=9+3x-3 | | 8x^3-20x-2x+5=0 | | .4x+4.2=.3x+2.6 | | (2x-9)+14=(3x-8) | | 7X=10X | | 12=2(x+1)-6 | | 3(3x-3)-2=5x-43 | | 2x+1/8=5/3 | | 4(x+3)=2x+46 | | -1/4+1= | | 12+2x=42 | | -2.9c=8.7 | | -7=5(4x+3)-2 | | -8x-6=-6x-12 | | y=-0/4+1 | | 3(2x-5)=x-45 | | 4(4x-14)+x=5x-20 | | 5x+15=-3x-49 | | x/4-5=27 | | 3+4(n+2)=2n+3(n+4) | | x(x-15)=3(x-27) | | 0.67x+3.0=0.84x | | 23+2b=3(b+8)-3 | | 2(5x-4)=6x+12 | | -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 |